2022
DOI: 10.1590/1980-5373-mr-2022-0204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicon Carbide and Alumina Reinforcement of Different Volume Fraction on Wear Characteristics of AL 7075 Hybrid Composites Using Response Surface Methodology

Abstract: This study investigates the wear performance of Hybrid composite of Aluminium Al 7075 (SiC/Al 2 O 3 ). The Reinforcements used for the Hybrid composite preparation are Silicon Carbide (SiC) and Aluminium Oxide (Al 2 O 3 ). Reinforcements are added in 5%, 10% and 15% in volume percentage in to aluminium alloy for composite preparation. The wear performance of the developed composites was analysed using dry sliding test apparatus. The effect of wear study parameters such as load, sliding distance, sliding veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…CAO et al [28] has discovered that the behavior of the reinforced particles changes with the processing parameters. GUKENDRAN et al [29] concluded that the introduction of reinforcements into aluminium enhances the mechanical properties of the composites considerably.…”
Section: Introductionmentioning
confidence: 99%
“…CAO et al [28] has discovered that the behavior of the reinforced particles changes with the processing parameters. GUKENDRAN et al [29] concluded that the introduction of reinforcements into aluminium enhances the mechanical properties of the composites considerably.…”
Section: Introductionmentioning
confidence: 99%